UNJUK KERJA MOTOR BAKAR PERTALITE DENGAN PENAMBAHAN BIOETHANOL DARI TETES TEBU - Purnama, Ari; Romdloni , Macrus Afif (Jurnal Rekayasa Mesin, 2024)
The rapid increase in the number of motorized vehicles has resulted in the depletion of the availability of fossil-based fuel oil. Bioethanol from sugarcane molasses waste is an alternative that can be applied to vehicles with the condition that it has 99.95% ethanol fuel grade. The study used a bioethanol sample fuel blend BE10 (Bioethanol 10%+90% Pertalite), and then conducted property testing and Gas Chromatography Mass Spectrometry (GCMS) to observe the compound structure of the fuel. Modification of the ignition timing forward 2o (+2) was done by reprogramming the Engine Control Module (ECM). The addition of up to 20% bioethanol to pertalite increased the octane number from 90 to 93.1. However, the heating value decreased from 42.5 to 39.18 MJ/kg. In the GC-MS test, the number of compounds in the fuel increased to 52 and 51 compounds, respectively. The highest improvement in engine performance of all parameters using bioethanol and advance ignition was sample (BE10+2). The thermal efficiency was 6.16%. Thus, the use of bioethanol fuel blends and ignition timing modifications can be applied to vehicles to get good performance and be more environmentally friendly.